Pemetaan Objek Wisata Dalam Pengembangan Sektor Pariwisata Di Dlingo, Bantul - Ninik Probosari; Sri Kussujaniatun; Anis Siti Hartati (Eksos LPPM, 2020)
The development of tourism sector is one of the efforts to excavate the revenue of Bantul regency. Dlingo subdistrict, Bantul has a potential for a high tourism sector. The tourism sector is very varied, even some local people who do not know about the potential tourism objects including tourist villages offered by Dlingo sub-district, such as Tourism village and nature tourism objects. If tourism in a region is mapped, it can know the types and potential of other natural tourism both in the stage of development and not yet developed, so that by the existence of tourism mapping can set the points Tourist attractions and make it easy for local and foreign tourists to choose the tourist attractions that they want to visit. The results of tourism mapping can determine the points of tourist attractions and make it easier for local and foreign tourists to choose the tourist attractions that they want to visit. Besides, the development of tourism potential will increase the income and income of the Community.